2016
DOI: 10.1210/en.2016-1642
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in the Dmp1 Gene Alters Phosphate Responsiveness in Mice

Abstract: Mutations in the dentin matrix protein 1 (DMP1) gene cause autosomal recessive hypophosphatemic rickets (ARHR). Hypophosphatemia in ARHR results from increased circulating levels of the phosphaturic hormone, fibroblast growth factor 23 (FGF23). Similarly, elevated FGF23, caused by mutations in the PHEX gene, is responsible for the hypophosphatemia in X-linked hypophosphatemic rickets (XLH). Previously, we demonstrated that a Phex mutation in mice creates a lower set point for extracellular phosphate, where an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…ARHR1 is caused by loss-of-function mutations in dentin matrix protein-1, which is required for normal mineralization of bone ( 18 ). It is currently believed that the excessive osteocytic and osteoblastic FGF23 secretion in both diseases is either driven by the impaired mineralization of the extracellular matrix, which may be detected by matrix-embedded bone cells through a putative sensing mechanism that may involve FGF receptors ( 19 , 20 ), or by an altered set point for phosphate sensing in bone cells ( 21 , 22 ). Circulating intact FGF23 is also elevated in patients with chronic kidney disease (CKD), and can reach blood levels as high as 1,000-fold above the normal range ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…ARHR1 is caused by loss-of-function mutations in dentin matrix protein-1, which is required for normal mineralization of bone ( 18 ). It is currently believed that the excessive osteocytic and osteoblastic FGF23 secretion in both diseases is either driven by the impaired mineralization of the extracellular matrix, which may be detected by matrix-embedded bone cells through a putative sensing mechanism that may involve FGF receptors ( 19 , 20 ), or by an altered set point for phosphate sensing in bone cells ( 21 , 22 ). Circulating intact FGF23 is also elevated in patients with chronic kidney disease (CKD), and can reach blood levels as high as 1,000-fold above the normal range ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Activating mutation in the Phex gene, the most common cause of hypophosphatemic rickets, occurs in 1:20,000 people and is inherited as X-linked ( 7 ). The common abnormality reported in both X-linked and autosomal recessive hypophosphatemic rickets is an increase in circulating FGF23 due to enhanced skeletal expression as demonstrated by Ichikawa et al ( 15 ) in the current issue of Endocrinology as well as by others. FGF23 interacts with the FGF receptor and Klotho to promote mitogen-activated protein kinase signaling and, thereby, decrease expression of Npt2a and Npt2c in renal tubular cells.…”
mentioning
confidence: 68%
“…In a study published in the current issue of Endocrinology (15), Econs and colleagues addressed the question of whether the set point for phosphate is also lowered in ARHR by using Dmp1 knockout mice, a murine model of ARHR. In the current study, the authors reported the presence of the same low extracellular phosphorus set point in Dmp1 null mice with the associated increase in both circulating and skeletal expression of Fgf23 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The exact role of DMP1 remains unknown, but recent murine experimental models have shown that mutations in the DMP1 gene create a lower set point for extracellular phosphate and maintain it through the regulation of FGF23 cleavage and expression. 11 …”
Section: Discussionmentioning
confidence: 99%